Flail chest in a polytraumatized patient: management and treatment – case report - Milošević, Bojan; Milisavljević, Slobodan; Dončić, Nikola; Arsenijević, Miloš; Mrvić, Stanko; Stojković, Dragan; Marić, Nebojša; Spasić, Marko (Vojnosanitetski pregled, 2017)
Introduction. Management of a polytraumatized patient is a problem that requires a multidisciplinary approach, in order to optimise patient’s outcome. The purpose of this study was to show the approach in the treatment of a patient with a severe life-threatening polytrauma, including a personalized healthcare approach with the positive outcome after the inadequate initial treatment. Case report. We presented a case of a young polytraumatized patient with trauma as a result of road traffic accident. The patient had chest, abdominal and right arm injuries. He was diagnosed of hepatic rupture with conquasation and retroperitoneal hematoma and the patient underwent liver tamponade. Chest trauma due to bilateral serial rib fracture with flail chest was treated by chest drainage. After the adequate multidisciplinary interventions for the patient, the patient was discharged. Conclusion. This case report is of great importance since it shows that severe polytraumatized patients with bad initial prognosis can successfully receive a life-saving treatment.